Performance Evaluation of MANET Routing Protocols for Varying Topologies Size - Awos Kh. Ali (College of Education for Pure Sciences, 2012)
ABSTRACT Mobile ad-hoc network (MANET) is a collection of wireless mobile hosts forming a temporary network without the centralized administration or base station. Mobile ad-hoc network have the attributes such as wireless connection, continuously changing topology, ease of deployment. This study has compared the performance of two MANET routing protocol DSDV and TORA by using random mobility model. In this study two performance metrics have been chosen, such as Average Delay and throughput. The simulations are carried out on NS-2. The performance differentials are analyzed using varying network size (20 and 50 nodes) and simulation time was 100s. Simulation results confirm that DSDV performs well in terms of Average Delay. But TORA performs better than DSDV in terms of throughput and changing in network topology.